A VLT/MUSE analysis of HeIIλ1640 emitters at z = 2 – 4. Issue Volume 15:Issue S352(2019) (June 2019) - Nanayakkara, Themiya
Abstract: In the quest to study early star-formation physics in the universe, one of the most sought after tracers is HeIIλ1640, with its presence in the lack of other metal emission/absorption lines generally being interpreted as evidence for metal-poor stellar populations. HeII ionizing photons are produced via sources of hard ionizing radiation and requires photons with energies ⩾ 54.4eV, however, traditional stellar population models lack sufficient ionising photons to match with current observations. Our analysis of z = 2 – 4 HeIIλ1640 emitters from deep 10-30h pointings from MUSE has shown that ISM properties inferred from multiple rest-UV diagnostics are not compatible with requirements necessary to reproduce HeIIλ1640 equivalent-widths. Thus, we have used latest generation of single, rotational, and binary stellar population models with realistic dust physics to explore rest-UV emission line diagnostics and link with H and He + ionisation photon production efficiencies (ξion (H, He + )) in a variety of stellar/gas metallicities and star-formation histories. I will discus our latest results and show that including 'exotic' stellar phenomena such as extreme low-metallicity binary stars, X-ray binaries, and dust dissociation physics may be necessary to lessen the tension between models and observations.